2008
DOI: 10.16997/jdd.74
|View full text |Cite
|
Sign up to set email alerts
|

Is Information Good for Deliberation? Link-Posting in an Online Forum

Abstract: Does information improve deliberation? Proponents of online deliberation argue that the availability of the Internet can solve two longstanding problems of citizen decisionmaking: that preexisting inequalities tend to be reproduced rather than minimized in deliberative forums and that citizen decisionmaking sacrifices the benefits of expertise. Because all deliberators online can access information during their discussion, deliberation should be more informed and more equal. We put those claims to the test by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Scholars also have investigated whether deliberative forums can narrow information gaps between participants, documenting mixed results (Fraile, 2014;Karpowitz, Raphael & Hammond, 2009;PytlikZillig et al, 2017). At least one experiment demonstrated that certain formats exacerbated knowledge inequalities (Polletta, Chen & Anderson, 2008).…”
Section: Democracy's Knowledge Problemmentioning
confidence: 99%
“…Scholars also have investigated whether deliberative forums can narrow information gaps between participants, documenting mixed results (Fraile, 2014;Karpowitz, Raphael & Hammond, 2009;PytlikZillig et al, 2017). At least one experiment demonstrated that certain formats exacerbated knowledge inequalities (Polletta, Chen & Anderson, 2008).…”
Section: Democracy's Knowledge Problemmentioning
confidence: 99%
“…Hosting one such panel online affords certain deliberative benefits. As just one example, by sharing links and referencing discussions occurring outside of the deliberative forum, participants with minority opinions within the group can legitimize their opinions by accessing a wider range of ideas through online resources (Polletta et al, 2009). Like any communication medium, however, online forums have limitations, including problems of source credibility, Internet literacy, and personal accountability (especially in anonymous forums).…”
Section: Justificationmentioning
confidence: 99%